Association between the GHR, GHRHR and IGF1 gene polymorphisms and milk coagulation properties in Sarda sheep. Issue 3 (10th July 2019) - Dettori, Maria L.; Pazzola, Michele; Pira, Emanuela; Stocco, Giorgia; Vacca, Giuseppe M.
Abstract: We investigated whether variation of the sheep Growth Hormone Receptor ( GHR ), Growth Hormone Releasing Hormone Receptor ( GHRHR ) and Insulin-Like Growth Factor 1 ( IGF1 ) genes were associated with milk coagulation properties (MCP) in sheep. The GHR, GHRHR and IGF1 genes are part of the GH system, which is known to modulate metabolism, growth and reproduction as well as mammogenesis and galactopoiesis in dairy species. A total of 380 dairy Sarda sheep were genotyped for 36 SNPs mapping to these three genes. Traditional MCP were measured as rennet coagulation time (RCT), curd-firming time ( k 20 ) and curd firmness at 30 m ( a 30 ). Modeling of curd firming over time (CF t ) was based on a 60 m lactodynamographic test, generating a total of 240 records of curd firmness (mm) for each milk sample. The model parameters obtained included: the rennet coagulation time as a result of modeling all data available (RCTeq, min); the asymptotic potential value of curd firmness (CFP, mm) at an infinite time; the CF instant rate constant ( k CF, %/min); the syneresis instant rate constant ( k SR, %/min); the maximum value of CF (CFmax, mm) and the time at achievement of CFmax ( t max, min). Statistical analysis revealed that variation of the GHR gene was significantly associated with RCT, k SR and CFP ( P < 0.05). No other significant associations were detected. These findings may be useful for the dairy industry, as well as for selection programs.